ANALISIS DAN SIMULASI KINERJA SIMPANG EMPAT INSPEKTUR MARZUKI KOTA PALEMBANG DENGAN METODE PKJI 2023 DAN PTV VISSIM 8.0.2 - Yules Pramona Zulkarnain; Hariman Al Faritzie; Fira Oktavia; Ammar Asyraf; Togar Partahi Oloan (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2026)
The Inspektur Marzuki Four-Legged Intersection in Palembang City is an unsignalized intersection that frequently experiences congestion, especially during peak hours. This study aims to analyze the performance of the intersection using the Indonesian Road Capacity Guidelines (PKJI) 2023 and micro simulation through the PTV VISSIM 8.0.2. The data used consist of primary data, including road geometry, traffic volume, vehicle speed, side friction, and delay, as well as secondary data, including maps and site drawings of the intersection and information on the surrounding conditions such as the presence of public facilities and commercial activities.The parameters analyzed include degree of saturation (DS), average delay (T), queue probability (Pa), queue length, and level of service (LOS). Based on the PKJI 2023 method, the highest DS was found to be 0.68 SMP/hour, with an average delay of 11.70 seconds/vehicle and queue probability ranging between 19%–39%. Simulation results using PTV VISSIM showed an average delay of 6.43 seconds/vehicle, an average maximum queue length of 23.86 meters, and an overall LOS in category A.